Some trends in electronic publication and open access in Portuguese history journals - Guardado, Maria Cristina
In the last decades, ICT development and the use of computer networks led to major changes in the way scientists communicate the results of their researches. One of the most important transformations occurred in scholarly communication through the acceleration in the unbounded disclosure of scientific information (open access). However, the adoption of new channels varies according to the scientific areas. This study is part of an ongoing research that aims to understand the impact of digital media in the mechanisms of production and dissemination of scientific knowledge within a specific scientific community: historians. This paper will look at whether and how the history journals in Portugal are adopting electronic publishing and providing open access to their contents. To operationalise the study, thirteen R&D Units were contacted and asked to provide a list of the journals published and the format used. Furthermore, the Directory of Open Access Journals (DOAJ), Latindex and European Reference Index for the Humanities (ERIH) were researched. Finally, the websites of Portuguese higher education institutions with History Departments were consulted, with the aim of identifying any periodicals that might not have been previously identified. At the end, twenty-two titles were considered. Data seems to show that universities and History R&D Units increasingly value the free electronic access to research results produced by historians.